Osthole alleviates inflammation by down-regulating NF-κB signaling pathway in traumatic brain injury. (4th March 2019) - Kong, Liang; Yao, Yingjia; Xia, Yang; Liang, Xicai; Ni, Yingnan; Yang, Jingxian
Abstract: Traumatic brain injury (TBI) is a common neurotrosis disorder of the central nervous system (CNS), which has dramatic consequences on the integrity of damaged tissue. In this study, we investigated the neuroprotective effect and anti-inflammatory actions of osthole, a natural coumarin derivative, in both in vivo and in vitro TBI models. We first prepared a mouse model of cortical stab wound brain injury, investigated the capacity for osthole to prevent secondary brain injury and further examined the underlying mechanism. We revealed that osthole significantly improved the neurological function, increased the number of neurons beside injured site. Additionally, osthole treatment reduced the expression of microglia and glial scar, lowered the level of the proinflammatory cytokines interleukin (IL)-6, IL-1β, and tumor necrosis factor-α (TNF-α), and blocked the activation of nuclear factor kappa B (NF-κB). Furthermore, the protective effect of osthole was also examined in SH-SY5Y cells subjected to scratch injury. Treatment of osthole prominently suppressed cell apoptosis and inflammatory factors release by blocking injury-induced IκB-α phosphorylation and NF-κB translocation, and upregulated the IκB-α which functions in the NF-κB signaling pathway of SH-SY5Y cells. However, NF-κB signaling pathway was inhibited by pyrrolidine dithiocarbamate (PDTC), an NF-κB inhibitor, the anti-inflammatory effect of osthole was abolished. In conclusion, our findings demonstrated that osthole attenuated inflammatory response by inhibiting the NF-κB pathway in TBI.